2009
DOI: 10.1183/09031936.00125608
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in matrix metalloproteinase genes and lung cancer chemotherapy response and prognosis

Abstract: The prognosis for lung cancer patients treated with chemotherapy is poor. Single nucleotide polymorphisms (SNPs) in matrix metalloproteinase (MMP) genes could influence treatment outcome by altering apoptotic pathways. Eight SNPs with known or suspected phenotypic effect in six genes (MMP1, MMP2, MMP3, MMP7, MMP9 and MMP12) were investigated.For 349 Caucasian patients with primary lung cancer, receiving first-line chemotherapy, three different endpoints were analysed: response after the second cycle, progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
0
15
1
Order By: Relevance
“…For example, −1607 1G/2G was significantly associated with disease-free or overall survivals in patients with epithelial ovarian cancer [24], colorectal cancer [13]. However, the significant association was not found in breast cancer [18], esophageal adenocarcinoma [17] and lung cancer [25]. In the present study, we did not observe significant association of this variant with melanoma overall survival and the six clinicopathologic factors.…”
Section: Discussioncontrasting
confidence: 64%
“…For example, −1607 1G/2G was significantly associated with disease-free or overall survivals in patients with epithelial ovarian cancer [24], colorectal cancer [13]. However, the significant association was not found in breast cancer [18], esophageal adenocarcinoma [17] and lung cancer [25]. In the present study, we did not observe significant association of this variant with melanoma overall survival and the six clinicopathologic factors.…”
Section: Discussioncontrasting
confidence: 64%
“…Furthermore, MMP-2 strongly contributes to prostate carcinogenesis (Littlepage et al, 2010) and in the vast majority of cases MMP-2 up-regulation is associated to poor prognosis (Offersen et al, 2010;Zhong et al, 2008). MMP-2 and cancer further registers a validation from genetic and epigenetic factors, since polymorphisms (SNPs) in the MMP-2 gene directly correlates with the pathology (Chaudhary et al, 2010;Kang et al, 2011;Scherf et al, 2010).…”
Section: Biological Aspectsmentioning
confidence: 99%
“…An SNP analysis of eight SNPs in six genes ( MMP1 , MMP2 , MMP3 , MMP7 , MMP9 , MMP12 ) revealed that small cell lung cancer patients carrying the G allele of the –82A/G MMP12 polymorphism, which is associated with a higher gene expression in reporter gene assays [74], had a significantly prolonged overall survival compared to patients with the common allele [75]. Based on the aforementioned findings, we can conclude that the role of MMP‐12 in cancer is as yet not fully understood.…”
Section: Mmp‐12 (Table 2)mentioning
confidence: 99%